MODEL PENGAWASAN ORANG TUA TERHADAP PENGGUNAAN MEDIA DIGITAL ANAK - Mazdalifah Mazdalifah; Moulita Moulita (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Children nowdays have easely access to information technology, especially smartphones, tablets and personal computers. Therefore, parents take an important role in monitoring their children’s digital media use. The problem that will be explored in depth is how parents supervise the use of children's digital media. This study used a survey method, using a questionnaire as a means of capturing data. The number of respondents is 150 people who have the characteristics of the elderly (father or mother) who have school children at the kindergarten, elementary, junior high, high school and university levels, and use digital media. Respondents were scattered in several sub-districts, namely Medan Johor, Medan Amplas, Medan Selayang, Medan Denai, Medan Polonia and Medan Deli. The results showed that most of the parents perform passive supervision, namely limiting the time the child uses the media and monitoring what sites the child visits. A small proportion of them conduct active supervision such as teaching and directing children to use digital media, especially the internet, and using the internet together with children. The parental supervision model of the effective use of children's digital media is an active supervision model, where parents are actively involved in supervising, not just supervising it.